Improved NO reduction by using metal–organic framework derived MnOx–ZnO. Issue 53 (27th August 2020) - Zhao, Ling; Chen, Ziang; Zhang, Peng; Zhang, Yu
Abstract : Derivatives based on metal frameworks (MOFs) are attracting more and more attention in various research fields. Abstract : Derivatives based on metal frameworks (MOFs) are attracting more and more attention in various research fields. MOF-based derivatives x % MnO x –ZnO are easily synthesized by the thermal decomposition of Mn/MOF-5 precursors. Multiple technological characterizations have been conducted to ascertain the strengthening interaction between Mn species (Mn 2+ or Mn 3+ ) and Zn 2+ ( e.g., XRD, FTIR, TG, XPS, SEM, H2 -TPR and Py-FTIR). The 5% MnO x –ZnO exhibits the highest NO conversion of 75.5% under C3 H6 -SCR. In situ FTIR and NO-TPD analysis showed that monodentate nitrates, bidentate nitrates, bridged bidentate nitrates, nitrosyl groups and C x H y O z species were formed on the surface, and further hydrocarbonates or carbonates were formed as intermediates, directly generating N2, CO2 and H2 O.